Corrigendum to: Mapping the Progress of Technological Pedagogical and Content Knowledge Research: Bibliometric Analysis - Prihantini Prihantini; Ai Rukmini; Ardhana Januar Mahardhani; Ratna Rintaningrum; Prihantini Prihantini; Ai Rukmini; Ardhana Januar Mahardhani; Ratna Rintaningrum (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The authors regret that there was a change in the authorship of the original article. The correct list of authors should read as follows: Prihantini, Ai Rukmini, Ardhana Januar Mahardhani, and Ratna Rintaningrum. Amalia Mustika has been removed from the author list at the request and with the agreement of all authors, including Amalia Mustika. This correction has been approved by the journal editor. The authors apologize for any inconvenience caused.